The European Union at the United Nations Intersecting Multilateralisms - Laatikainen, K.; Laatikainen, K.; Smith, K.; Smith, K. (Palgrave Studies in European Union Politics,, 2006)
This is the first book to examine in-depth the EU's relationship with the UN and to analyze critically the EU's contribution to 'effective multilateralism'. The contributors show that the EU most often fails to make the UN as effective as it should be in addressing global challenges.